2020
DOI: 10.2147/ott.s238665
|View full text |Cite
|
Sign up to set email alerts
|

<p>Effects of miR-330-3p on Invasion, Migration and EMT of Gastric Cancer Cells by Targeting PRRX1-Mediated Wnt/β-Catenin Signaling Pathway</p>

Abstract: Background: miRNA, as a biological marker, had more and more attention in recent years due to the important role it plays in cancer. Currently, there are extensive studies on miRNAs, among which miR-330-3p is reported to be implicated in the pathophysiological processes of various cancers. However, little progress has been made in the mechanism of miR-330-3p in gastric cancer. Objective: To explore the expression and relevant mechanism of miR-330-3p and PRRX1 in gastric cancer (GC). Methods: Forty-five GC pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The occurrence of gastric cancer is a multistage and multifactorial pathological process involving gene mutations, epigenetic changes, and abnormal molecular signaling pathways [16]. miRNAs affect the stability and translation of target mRNAs and regulate processes such as cell cycle [17], proliferation [18], apoptosis [19], migration [20], and invasion [21]. Recently, numerous studies have shown that abnormal expression of miRNAs is closely related to the occurrence, development, and metastasis of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of gastric cancer is a multistage and multifactorial pathological process involving gene mutations, epigenetic changes, and abnormal molecular signaling pathways [16]. miRNAs affect the stability and translation of target mRNAs and regulate processes such as cell cycle [17], proliferation [18], apoptosis [19], migration [20], and invasion [21]. Recently, numerous studies have shown that abnormal expression of miRNAs is closely related to the occurrence, development, and metastasis of gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…GC tissue samples [29] miR-330-3p Lymph node metastasis (p < 0.001). Serum, GC tissue samples [87] miR-361-5p…”
Section: Micrornamentioning
confidence: 99%
“…To further explore the molecular mechanism circ_0058063 mediated, we performed bioinformatics analysis and found miR-330-3p might be the target of circ_0058063. Previously, a crucial tumor suppressor of miR-330-3p was observed in many malignant tumors [11–13]. In this study, we explored the roles of cytoplasmic circ_0058063 in TC in vitro and in vivo .…”
Section: Introductionmentioning
confidence: 99%